THE USE OF DIRECTED READING THINKING ACTIVITY STRATEGY THROUGH LESSON STUDY ACTIVITY TOWARD STUDENTSâ READING COMPERHENSION - Suardi, Suardi; Geri, Rahmawati Eka (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2017)
This thesis aimed at finding out the application of Directed Reading Thinking Activity strategy in improving the studentsâ reading comprehension at the eighth grade of SMPN 2 Palopo. This research applied pre-experimental design and it was conducted for four meetings through lesson study activity in treatment process. The population of this research is 272 students. In determining the sample, the researcher used random sampling technique to choose sample and took class IIA consisted of 30 students. The instrument used to collect the data was narrative text. To collect the data the researcher used SPSS version 20. The researcher concluded that the application of Directed Reading Thinking Activity Strategy can improve studentsâ reading comprehension. It is proven by the significant difference between the studentsâ mean score in pretest and posttest. In pretest, the studentsâ mean score is 71.33 and the studentsâ mean score in posttest is 80.40. The researcher also finds that the P-value is 0.00 and the Î± I s 0.05, therefore P< Î± (0.00< 0.05). It is proven that the null hypothesis (H0) is rejected and alternative hypothesis (H1) is accepted. It means that used directed reading thinking activity strategy can improve studentsâ reading comprehension.